Care burden on family caregivers of patients with dementia and affecting factors in China: A systematic review - Wang, Lan; Zhou, Yang; Fang, Xiaofeng; Qu, Guiyu (Frontiers in Psychiatry, 2022)
Background: Dementia is a chronic and progressive illness featured with severe impairment and high dependencies. Under the influence of Chinese traditional culture, 80% of dementia patients are watched over at home with family caregivers as primary caregivers. However, long-term care brings formidable burdens to them and reduces the quality of their life. It is necessary to find out influencing factors of caregivers’ burden. Methods: A scoping search was conducted of the eight electronic databases from January 2010 to June 2022: PubMed, Embase, the Cochrane Library, Web of Science, CNKI, VIP, CBM, and WanFang Data. Research articles included in this review mentioned the affecting factors of family caregivers' care burden or stress, and the level of care burden was evaluated by a standardized care burden scale. Results: A total of 1888 related articles were found. 23 cross-sectional studies were eventually included. After quality assessment, 8 were of high quality and 15 were of moderate quality. Results were grouped into 3 factors categories: patient, caregiver and society. The severity of disease, self-care ability, neuropsychiatric symptoms, care time, health status, economic stress, psychological status, social support and age were reported in many previous studies. Conclusions: Family caregivers of dementia patients generally have burdens, and their affecting factors were diverse. The severity of disease, self-care ability, neuropsychiatric symptoms, care time, health status, economic stress, psychological status and social support were considered as main factors, but there was no conclusion on age. Taking all of these factors into consideration will help reduce caregivers’ burden.